Türk Ticaret Kanunu ve Tüketicinin korunması hakkında kanun açısından reklamlar - Çatakoğlu, Buket (My University, 2003)
Reklam, malların veya hizmetlerin satışını artırmak gibi ticari gayelerle ya da bir düşüncenin benimsetilmesi gibi manevi bir amaç güdülerek yapılan tanıtım faaliyetidir. Tüketicilere ulaştırılması için çeşitli araçlara başvurulan bu tanıtım faaliyeti karşılığında bir ücret ödenir. Ücret ödeyen kişi ya da kurumun kimliğini belirleyici ad, unvan, marka gibi öğelerin de reklamdan anlaşılabilmesi gerekir. Reklam şekil ve yolları sayısız olduğu halde, reklam konusunu reklamı yapılan şahsın veya şeyin adı oluşturur. Ticaret ünvanı, işletme adı, marka gibi ad ve işaretler, bu bağlamda reklam konusu olabilecek hukuki kurumlardır. Reklam aynı zamanda piyasa ekonomisinin temeli olan rekabetin de vazgeçilmez bir aracıdır. Doğru, dürüst olmayan ve dürüst rekabet ilkelerinin ihlal edildiği bir reklam, ekonomik rekabet hakkının kötüye kullanımına ve dolayısıyla haksız rekabete yol açar. Böyle bir reklam, rakibin ekonomik kişiliğini zedelediği gibi, tüketiciyi de yanıltarak zarar görmesine neden olur. Aldatıcı olarak nitelendirdiğimiz bu tür reklamlarla mücadelede, nihai karar verebilen bir organca yürütülen idari denetim ile bizzat reklam sektörünce uygulanan

denetim sistemlerine etkinlik kazandırılmalıdır. Advertisements are promotion activities executed with commercial purposes like increasing the sales of goods or services or with a moral intention like allowing appropriating a thought. A price is paid in return for this promotion activities applied with various means for reaching consumers. Constituents like name, title, or trademarks determining the identity of the price-paying person or institution must be detectable from the advertisement. Despite the fact that there are numerous forms and ways of advertising, the person or object advertised constitue the theme of the advertisement. In this context names and marks like commercial title, name of enterprise and trademarks are the legal institutions being potential advertisement themes. At the same time, advertisement is the indispensable means of competition, which is not true and honest, furthermore in which the honest competition principles are breached, gives rise to abuse of the economical right of competition and consequently to unfair competition. As like as such an advertisement bruises the economical identity of the competitor, it also causes damages to the consumer by misleading him. With regards to the fight with such advertisements, which we describe as deceptive, an administrative supervision executed by an organ authorized to take definite resolutions and self-control systems applied by the advertisement sector itself have to be caused gaining activity.
Keywords: Hukuk; Özel Hukuk; Reklam